Política industrial e redes de comércio de medicamentos: os casos do Brasil, Irlanda e Índia no período de 1995 a 2015 - Franculino, Kleber Alves Da Silva; Gomes, Rogério [UNESP]; Hasenclever, Lia (Instituto de Economia da Universidade Estadual de Campinas, 2021)
The level of industrial development of a nation can be inferred by the technological and productive domain of the country and its local productive structure. These elements are also important to determine the competitiveness of nations and their participation in international trade. The article empirically assesses how the development of the pharmaceutical industry is associated with changes in the patterns of specialization in the global medicines trade network to investigate the co-evolution of such dimensions in view of the industrial policy framework of three different countries: Ireland, India, and Brazil. The main results, obtained via the Network Analysis method, show that India and Ireland, unlike Brazil, have adopted more consistent and long-term policies, essential for the success of a sector development strategy, measured by their roles in the world trade network of medicines. Furthermore, the results make it clear that trade opening is not a sufficient condition for a country to reach higher levels of competitiveness.

O patamar de desenvolvimento industrial das nações pode ser inferido pelo domínio tecnológico e produtivo de um país e da sua estrutura produtiva local. Estes elementos são também importantes para determinar a competitividade das nações e a sua participação no comércio internacional. O artigo avalia empiricamente como o desenvolvimento da indústria farmacêutica está associado às mudanças nos padrões de especialização na rede de comércio mundial de medicamentos para investigar a coevolução de tais dimensões tendo em vista o arcabouço das políticas industriais de três países distintos: Irlanda, Índia e Brasil. Os principais resultados, obtidos pelo método de Análise de Redes, mostram que Índia e Irlanda, diferente do Brasil, adotaram políticas mais consistentes e contínuas, essenciais para o sucesso de uma estratégia de desenvolvimento do setor, mensurado por seus papéis na rede de comércio mundial de medicamentos. Além disso, os resultados deixam evidente que a abertura comercial não é condição suficiente para um país alçar patamares superiores de competitividade.
Industrial policy and pharmaceutical trade networks: cases in Brazil, Ireland and India from 1995 to 2015
Keywords: Industrial policy; Network analyses; Medicines world trade; Pharmaceutical industry; Política industrial; Análise de redes; Comércio mundial de medicamentos; Indústria farmacêutica